The influence of ego depletion on sprint start performance in athletes without track and field experience - Englert, Chris; Persaud, Brittany; Oudejans, Raoul; Bertrams, Alex (Frontiers in Psychology, 2015)
We tested the assumption that ego depletion would affect the sprint start in a sample of N = 38 athletes without track and field experience in an experiment by applying a mixed between- (depletion vs. non-depletion) within- (T1: before manipulation of ego depletion vs. T2: after manipulation of ego depletion) subjects design. We assumed that ego depletion would increase the possibility for a false start, as regulating the impulse to initiate the sprinting movement too soon before the starting signal requires self-control. In line with our assumption, we found a significant interaction as there was only a significant increase in the number of false starts from T1 to T2 for the depletion group while this was not the case for the non-depletion group. We conclude that ego depletion has a detrimental influence on the sprint start in athletes without track and field experience.